A solution to the 2-pyridyl organometallic cross-coupling problem: regioselective catalytic direct arylation of pyridine N-oxides. - Campeau, L; Rousseaux, S; Fagnou, K (2005)
Direct arylation reactions of pyridine N-oxides occur in excellent yield with complete selectivity for the 2-position with a wide range of aryl bromides. This reactivity permits the use of inexpensive, commercially available, and bench-stable pyridine N-oxides as replacements for problematic 2-metallapyridines in palladium-catalyzed cross-coupling reactions.